2016
DOI: 10.1016/j.drugalcdep.2016.08.636
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes, conventional cigarettes, and dual use in Korean adolescents and university students: Prevalence and risk factors

Abstract: Objective To examine risk factors associated with use of e-cigarettes only, conventional cigarettes only, and dual use in Korean adolescents and young adults. Methods In a cross-sectional study, anonymous questionnaires were completed between April-May, 2015 among 1) 2744 middle and high school students, aged 13–18, from Seoul, Incheon, Gyeonggi, and Cheongju, Korea and 2) 2167 university students, aged 19–29, from fourteen universities in Korea. Results The results show that 12.6% of adolescents and 21.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 19 publications
6
26
1
4
Order By: Relevance
“…Stratified by geographic location, the pooled effects for Europe, Australia, Asia and America, were 2.11 (95% CI=1.51-2.94), 2.11 (95% CI=1. 41 Figure S2).…”
Section: Friend Smoking and E-cigarette Use In Adolescentsmentioning
confidence: 99%
“…Stratified by geographic location, the pooled effects for Europe, Australia, Asia and America, were 2.11 (95% CI=1.51-2.94), 2.11 (95% CI=1. 41 Figure S2).…”
Section: Friend Smoking and E-cigarette Use In Adolescentsmentioning
confidence: 99%
“…Some advertisements describe electronic cigarettes as a healthier alternative to conventional cigarettes . As this perception of electronic cigarettes has become widespread throughout the culture, the number of electronic cigarette vapers has been growing rapidly . One prior study suggested that people choose electronic cigarettes as a smoking substitute; however, the risk of developing smoking‐related diseases, particularly periodontal diseases, could still be high, as there is a lack of research about the safety of electronic cigarettes .…”
Section: Introductionmentioning
confidence: 99%
“…There is emerging epidemiological evidence that a large proportion of adolescent e-cigarette users are dual users defined as those who report both e-cigarette use and cigarette smoking (Hughes et al, 2015; Jeon et al, 2016; Kristjansson et al, 2015). Furthermore, the most common reasons for e-cigarette use among adolescents are for experimentation and recreational purposes while adults were most likely to report using e-cigarettes for smoking cessation purposes (Hughes et al, 2015; Patel et al, 2016; Patrick et al, 2016).…”
Section: Introductionmentioning
confidence: 99%